THE UTILIZATION OF MILITARY POWER IN FOREIGN POLICY: A CASE STUDY OF THE ACCEPTANCE OF THE UNITED KINGDOM AS A DIALOGUE PARTNER FOR ASEAN - Kurniawan Firmuzi Syarifuddin; Anak Agung Banyu Perwita; Munif Prasojo (The Republic of Indonesia Defense University, 2022)
The acceptance of the United Kingdom as a new ASEAN dialogue partner ended the 22-year moratorium and stepped over several other countries. Becoming an ASEAN dialogue partner is one of the focuses of the United Kingdom's attention after leaving the European Union. To secure its national interests, the United Kingdom also restructured its defense strategy, which combined security, development, and foreign policy strategies in the Integrated Reviews. One of the military maneuvers carried out is ‘tilt’ to the Indo-Pacific Region as one of the new strategies. This article examines whether the United Kingdom military can play a crucial role in preparing a country's foreign policy regarding the acceptance of the United Kingdom as an ASEAN dialogue partner. A qualitative descriptive method has been chosen to complete the research through a case study approach. The study results that the various military deployment efforts carried out by the United Kingdom ultimately led to acceptance as an ASEAN dialogue partner. However, the research found that various supporting foreign policy factors must be comprehensively and interrelated to obtain an optimal foreign policy.